Gastric Ultrasound for the Regional Anesthesiologist and Pain Specialist. Issue 3 (September 2019) - Haskins, S.C.; Kruisselbrink, R.; Boublik, J.; Wu, C.L.; Perlas, A.
Abstract : ( Reg Anesth Pain Med . 2018;43:689–698) A significant cause of patient morbidity in the perioperative setting is pulmonary aspiration of gastric contents. Despite patients following the American Society of Anesthesiologists recommendations for fasting before a procedure, there is substantial variability in gastric-emptying time among patients. This may lead to a small percentage of patients that still have solid gastric contents at the time of operation. Gastric ultrasound has the potential to play an important role in the perioperative setting to provide reliable information regarding gastric content and assessment of aspiration risk.